Prediction of pathways and places of accumulation for hydrocarbons of the Chernigiv segment of the Dnieper-Donets aulacogene in relation to magnetic heterogeneity - M. I. Orlyuk; V. V. Drukarenko (Геофизический журнал, 2018)
A complex analysis of the magnetic inhomogeneity of the entire crustal section is performed in conjunction with the available geological and geophysical data on the prediction of migration paths of deep hydrocarbons and their accumulation in the upper part of the crystalline basement and sedimentary cover.